A phase I/Ib study of OTSGC-A24 combined peptide vaccine in advanced gastric cancer - Sundar, Raghav (BMC Cancer, 2018)
BACKGROUND: We conducted a phase I/Ib, open-label, single-arm trial to assess the safety, tolerability and optimal scheduling regimen of OTSGC-A24 cancer vaccine in patients with advanced gastric cancer. METHODS: Patients with advanced gastric cancer with HLA-A*24:02 haplotype were included in this study. OTSGC-A24 was administered at 1 mg in 3-weekly (3w), 2-weekly (2w), and weekly (1w) cohorts to evaluate the safety, immunological response and schedule. Based on the highest specific cytotoxic T lymphocyte (CTL) induction rate at 4 weeks, using the ELISPOT test, cohorts were expanded to define the optimal dosing schedule for OTSGC-A24. RESULTS: In this study, 24 advanced gastric cancer patients with HLA-A*24:02 haplotype were enrolled and treated in 3 cohorts (3w cohort: 3; 2w cohort: 11 and 1w cohort: 10 patients). The most common adverse events were decreased appetite (29%), diarrhea (21%), myalgia (25%). The most common treatment-related adverse event was injection site erythema (25%). No dose-limiting toxicities were observed in any cohort and OTSGC-A24 was well tolerated. Positive CTL responses after vaccination were observed in 15 patients (75%) at 4 weeks: 3w cohort (33%), 2w cohort (88%), 1w cohort (78%). At 12 weeks, 18 patients had responded (90%); 3w cohort (100%), 2w cohort (100%), 1w cohort (78%). The best radiological was stable disease (40%). Median progression free survival was 1.7 months (95% CI: 1.4 to 3.5) and median overall survival was 5.7 months (95% CI 3.8 to 8.6). CONCLUSIONS: OTSGC-A24 combined peptide cancer vaccine was well tolerated. Significant responses in CTL were observed and the recommended phase 2 dose is 1 mg OTSGC-A24 sub-cutaneous, every 2 weeks. Although no radiological response was observed, a respectable overall survival was achieved, consistent with other immunotherapy agents being investigated in gastric cancer. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01227772, Date registered: 21 Oct 2010.